Use of alternatives to PFOS, its salts and PFOSF for the control of leaf-cutting ants Atta and Acromyrmex. Issue 2 (28th March 2016) - Britto, Júlio Sérgio de; Forti, Luiz Carlos; Oliveira, Marco Antonio de; Zanetti, Ronald; Wilcken, Carlos Frederico; Zanuncio, José Cola; Loeck, Alci Enimar; Caldato, Nádia; Nagamoto, Nilson Satoru; Lemes, Pedro Guilherme; Camargo, Roberto da Silva
No abstract available